Multiscale simulation of elongated particles in fluidised beds. (May 2019) - Fitzgerald, Barry W.; Zarghami, Ahad; Mahajan, Vinay V.; Sanjeevi, Sathish K.P.; Mema, Ivan; Verma, Vikrant; El Hasadi, Yousef M.F.; Padding, Johan T.
Highlights: Multiscale approach for elongated particles in fluidised bed reactors. Motivated by separation of length scales between particle and industrial scale. Relevance of DNS results for hydrodynamic forces and boundary effects. Key aspects for simulating elongated particles with CFD-DEM are presented. Propose changes to industrial-scale models for elongated particles in fluidised beds. Abstract: In this paper, we present a number of key numerical methods that can be used to study elongated particles in fluid flows, with a specific emphasis on fluidised beds. Fluidised beds are frequently used for the production of biofuels, bioenergy, and other products from biomass particles, which often have an approximate elongated shape. This raises numerous issues in a numerical approach such as particle-particle contact detection and the accurate description of the various hydrodynamic forces, such as drag, lift, and torque, that elongated particles experience when moving in a fluid flow. The modelling is further complicated by a separation of length scales where industrial flow structures that can extend for many metres evolve subject to solid-solid and solid-fluid interactions at the millimetre scale. As a result, it is impossible to simulate both length scales using the same numerical approach, and a multiscale approach is necessary. First, we outline the direct numerical simulation (DNS) approach that may be employed to estimate hydrodynamic force closures for elongated particles in a fluid flow. We then describe the key aspects of a CFD-DEM approach, which can be used to simulate laboratory scale fluidisation processes, that must be addressed to study elongated particles. Finally, we briefly consider how current industrial-scale models, which concretely assume particle sphericity, could be adapted for the simulation of large collections of elongated particles subject to fluidisation.